Lipin‐1 regulates Bnip3–mediated mitophagy in glycolytic muscle. Issue 12 (25th June 2018) - Alshudukhi, Abdullah A.; Zhu, Jing; Huang, Dengtong; Jama, Abdulrahman; Smith, Jeffrey D.; Wang, Qing Jun; Esser, Karyn A.; Ren, Hongmei
ABSTRACT: Autophagy of mitochondria (mitophagy) is essential for maintaining muscle mass and healthy skeletal muscle. Patients with heritable phosphatidic acid phosphatase lipin‐1–null mutations present with severe rhabdomyolysis and muscle atrophy in glycolytic muscle fibers, which are accompanied with mitochondrial aggregates and reduced mitochondrial cytochrome c oxidase activity. However, the underlying mechanisms leading to muscle atrophy as a result of lipin‐1 deficiency are still not clear. In this study, we found that lipin‐1 deficiency in mice is associated with a marked accumulation of abnormal mitochondria and autophagic vacuoles in glycolytic muscle fibers. Our studies using lipin‐1–deficient myoblasts suggest that lipin‐1 participates in B‐cell leukemia (BCL)‐2 adenovirus E1B19 kDa protein–interacting protein 3 (Bnip3)–regulated mitophagy by interacting with microtubule‐associated protein 1A/1B‐light chain (LC)3, which is an important step in the recruitment of mitochondria to nascent autophagosomes. The requirement of lipin‐1 for Bnip3–mediated mitophagy was further verified in vivo in lipin‐1–deficient green fluorescent protein‐LC3 transgenic mice (lipin‐1 –/– ‐GFP‐LC3). Finally, we showed that lipin‐1 deficiency in mice resulted in defective mitochondrial adaptation to starvation‐induced metabolic stress and impaired contractile muscle force in glycolytic muscle fibers. In summary, our study suggests that deregulated mitophagy arising from lipin‐1 deficiency is associated with impaired muscle function and may contribute to muscle rhabdomyolysis in humans.—Alshudukhi, A. A., Zhu, J., Huang, D., Jama, A., Smith, J. D., Wang, Q. J., Esser, K. A., Ren, H. Lipin‐1 regulates Bnip3–mediated mitophagy in glycolytic muscle. FASEB J. 32, 6796–6807 (2018). www.fasebj.org